Latent profile analysis on the decent work of Chinese employees: applying the Psychology of Working theory - Wang, Shengnan; Feng, Kai; Chu, Fengyuan; Li, Yongxin; Zhao, Guoxiang (Frontiers in Public Health, 2024)
Background: This study used a person-centred approach to identify the specific performance of decent work in various groups to determine the heterogeneity of its five dimensions. Method: The Decent Work Scale, Work Need Satisfaction Scale, Socioeconomic Status Scale, Job Satisfaction Scale, and Life Well-being Scale were used to conduct a network survey of organisations in various industries in Mainland China. A total of 1,000 questionnaires were distributed, and 780 valid responses were obtained. Results: The results showed that the decent work of participants could be divided into three types: low salary, low free time, and high decent work. The results showed no significant difference in age among the groups, whereas the differences in socioeconomic status were significant. Welch’s test was used to determine differences in the positive outcomes of the three potential types of decent work, and the results showed significant differences in work need satisfaction, job satisfaction, and life well-being among all groups. Conclusion: This study examined the characteristics of decent work more realistically, showing that decent work is not an all-or-nothing structure and that its intrinsic components should be flexibly combined according to the research background and purpose.